An Assessment of impact of block chain on UAE economic mechanism: Examining the Impact of Blockchain Technology on UAE's Economic Mechanisms (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Adoption of technology by a nation to enhance living standards, ease of doing business, andtransparency offers the country a competitive edge. Technologies are assisting nations in a variety ofways to boost economic development by lowering manufacturing costs, introducing new enterprises, andadvancing communication. This research tried to examine the influence of block chain technology on theUAE's economic mechanisms. Furthermore, the influence of resident comprehension of block chain onUAE economic mechanisms was studied. According to the study, the UAE government is keen to deployblock chain technology in all fields. However, we can estimate its level of readiness based on theresponses. Using blockchain technology for economic development, on the other hand, offers enormousgrowth and development potential. This has already had an impact on the UAE's government andbusiness sectors. However, as seen by the 4 score, block chain technology is thriving in the UAE. With amarginal rate of 0.89, blockchain technology has a significant impact on economic activity in the UAE,affecting both the public and commercial sectors.